The joint effects of loneliness and interpersonal abuse on suicidal thoughts and behaviors among young adults in higher education in the United States - Hans Oh; André Hajek; Jinyu Du; Lee Smith; Edouard Leaune; Louis Jacob (BMC Psychology)
Abstract Background Loneliness and interpersonal abuse are two factors that contribute to suicide risk, but studies exploring their interactions on suicidal thoughts and behaviors are lacking. Thus, our aim was to examine potential synergies between loneliness and interpersonal abuse among young adults in higher education. Methods We analyzed data from the Healthy Minds Study (2020–2021; N = 101,744) and used multivariable logistic regression models to show the interaction between loneliness (UCLA 3-item Loneliness Scale) and interpersonal abuse (verbal, physical, and/or sexual) on suicidal thoughts and behaviors (suicidal ideation, suicide plans, suicide attempts), adjusting for age, gender, race/ethnicity, depression, anxiety, and food insecurity. Results Those who only reported being lonely had significantly greater odds of suicidal ideation (aOR: 3.01; 95% CI: 2.72–3.33), and those who only reported interpersonal abuse also had greater odds (aOR: 2.97; 95% CI: 2.52–3.50), when compared to those who reported neither. However, those who endorsed both loneliness and interpersonal abuse had the greatest odds (aOR: 5.65; 95% CI: 5.09–6.27), exceeding the sum of these individual effects. A similar and more pronounced pattern emerged for suicide plans and suicide attempts. Conclusion A synergy exists between loneliness and interpersonal abuse in relation to suicidal thoughts and behaviors among young adults in higher education.